Tweeting the Jihad: Social Media Networks of Western Foreign Fighters in Syria and Iraq - Klausen, Jytte (Studies in conflict and terrorism, 2015)
Social media have played an essential role in the jihadists' operational strategy in Syria and Iraq, and beyond. Twitter in particular has been used to drive communications over other social media platforms. Twitter streams from the insurgency may give the illusion of authenticity, as a spontaneous activity of a generation accustomed to using their cell phones for self-publication, but to what extent is access and content controlled? Over a period of three months, from January through March 2014, information was collected from the Twitter accounts of 59 Western-origin fighters known to be in Syria. Using a snowball method, the 59 starter accounts were used to collect data about the most popular accounts in the network-at-large. Social network analysis on the data collated about Twitter users in the Western Syria-based fighters points to the controlling role played by feeder accounts belonging to terrorist organizations in the insurgency zone, and by Europe-based organizational accounts associated with the banned British organization, Al Muhajiroun, and in particular the London-based preacher, Anjem Choudary.